2022
DOI: 10.3389/fbioe.2022.1098021
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of enhanced ethanol tolerance associated with hfq overexpression in Zymomonas mobilis

Abstract: Zymomonas mobilis is a promising microorganism for industrial bioethanol production. However, ethanol produced during fermentation is toxic to Z. mobilis and affects its growth and bioethanol production. Although several reports demonstrated that the RNA-binding protein Hfq in Z. mobilis contributes to the tolerance against multiple lignocellulosic hydrolysate inhibitors, the role of Hfq on ethanol tolerance has not been investigated. In this study, hfq in Z. mobilis was either deleted or overexpressed and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Similarly, reduced chemotaxis activity helps the cell adapt to its environment and allocate resources more wisely under stressful conditions. This aligns with previous studies that have shown down-regulation of flagellar biosynthesis in response to stress, suggesting a conserved strategy among bacteria [ 31 , 32 ]. Up-regulation of transporter proteins: Several transporter protein genes, such as molybdate ( modA , modB ), osmoprotectant ( opuBC , opuBB , opuBA ), biotin ( bioY ), and zinc/manganese/iron (II), were significantly up-regulated in the ABC transporters system (Additional file 3 : Table S4).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, reduced chemotaxis activity helps the cell adapt to its environment and allocate resources more wisely under stressful conditions. This aligns with previous studies that have shown down-regulation of flagellar biosynthesis in response to stress, suggesting a conserved strategy among bacteria [ 31 , 32 ]. Up-regulation of transporter proteins: Several transporter protein genes, such as molybdate ( modA , modB ), osmoprotectant ( opuBC , opuBB , opuBA ), biotin ( bioY ), and zinc/manganese/iron (II), were significantly up-regulated in the ABC transporters system (Additional file 3 : Table S4).…”
Section: Discussionsupporting
confidence: 91%
“…This aligns with previous studies that have shown down-regulation of flagellar Fig. 7 Batch fermentation of recombinant strain BS03-phaCBA in a 7.5 L bioreactor for the production of acetoin biosynthesis in response to stress, suggesting a conserved strategy among bacteria [31,32]. Up-regulation of transporter proteins: Several transporter protein genes, such as molybdate (modA, modB), osmoprotectant (opuBC, opuBB, opuBA), biotin (bioY), and zinc/manganese/iron (II), were significantly up-regulated in the ABC transporters system (Additional file 3: Table S4).…”
Section: Discussionsupporting
confidence: 90%
“…All plasmids were assembled by the Gibson Assembly method (Gibson et al, 2009). After purification, gene and vector fragments were ligated through the T5 exonuclease (NEB, WA, United States)dependent DNA assembly method as described previously (Tang et al, 2022). After transformation in E. coli, the correct colonies were selected by colony PCR and confirmed by Sanger sequencing (Tsingke Biotechnology, Beijing, China).…”
Section: Genetic Manipulation and Recombinant Strain Constructionmentioning
confidence: 99%
“…Hfq is an RNA-binding protein that regulates gene expression during post-transcriptional levels. Hfq plays various functions in the RNA metabolism of bacteria, including stabilizing small non-coding RNAs (sRNAs) and aiding in their interactions with messenger RNAs (mRNAs), which consequently impact the stability and translation of the specific targeted mRNAs [ 90 ]. This protein is homologous to Lms proteins found in eukaryotic cells in both functions and structures.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, overexpression of hfq resulted in tolerance of Z. mobilis to ethanol stress, which was attributed to the downregulation of genes related to flagellar biosynthesis and heat stress response proteins. Additionally, there was an upregulation of genes related to sulfate assimilation and cysteine biosynthesis, leading to a reduction in reactive oxygen species induced during ethanol stress [ 90 ].…”
Section: Introductionmentioning
confidence: 99%